Designing Art Center in Medan with Metaphor Architecture Theme - Maureen Nisha Alifia; Dwira Nirfalini Aulia (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
This thesis aims to design an Art Center in Medan City with a metaphor architectural approach. Medan City, as one of the cultural centers in North Sumatra, needs adequate facilities to support the rapid development of art and culture. The Art Center's design will integrate space needs for various arts and cultural activities such as art galleries, theaters, exhibition halls, workshops, and visitor-friendly public areas.The design approach used is Metaphor architecture which emphasizes the use of modern and innovative materials and design elements.